Tobacco Transcription Factor NtWRKY12 Interacts with TGA2.2 in vitro and in vivo - van Verk, Marcel; Neeleman, Lyda; Bol, John; Linthorst, Huub (Frontiers in Plant Science, 2011)
The promoter of the salicylic acid-inducible PR-1a gene of Nicotiana tabacum contains binding sites for transcription factor NtWRKY12 (WK-box at position -564) and TGA factors (as-1-like element at position -592). Transactivation experiments in Arabidopsis protoplasts derived from wild type, npr1-1, tga256 and tga2356 mutant plants revealed that NtWRKY12 alone was able to induce a PR-1a::β-glucuronidase (GUS) reporter gene to high levels, independent of co-expressed tobacco NtNPR1, TGA2.1, TGA2.2 or endogenous Arabidopsis NPR1, TGA2/3/5/6. By in vitro pull-down assays with GST and Strep fusion proteins and by Fluorescence Resonance Energy Transfer assays with protein-CFP and protein-YFP fusions in transfected protoplasts, it was shown that NtWRKY12 and TGA2.2 could interact in vitro and in vivo. Interaction of NtWRKY12 with TGA1a or TGA2.1 was not detectable by these techniques. A possible mechanism for the role of NtWRKY12 and TGA2.2 in PR-1a gene expression is discussed.